Strengthening Institutional Resilience in Public Organizations: The Role of Dynamic Capabilities and Innovative Leadership in the Digital Era (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Digital revolution and the disruption of the global labor market have made public organizations, especially vocational training institutions, even more complicated. This study seeks to examine the impact of dynamic skills on institutional resilience, with innovative leadership serving as a mediating variable. The study employed a quantitative methodology, utilizing data collected from 180 employees at the Medan Vocational and Productivity Training Center (BBPVP). We used Structural Equation Modeling based on Partial Least Squares (SEM-PLS) to look at the data. The findings indicate that dynamic capabilities exert a positive and significant influence on institutional resilience, underscoring the necessity for an organization to identify, capitalize on opportunities, and adapt to change. Dynamic qualities also have a big effect on inventive leadership, which is very important for making organizational change happen. Innovative leadership demonstrably influences institutional resilience and serves as a partial mediator between dynamic capabilities and institutional resilience. This research offers a theoretical advancement by synthesizing institutional theory, dynamic capacities, and innovative leadership to elucidate public organizational resilience. In practical terms, the findings of this study have significant significance for enhancing the adaptive capacity of vocational training institutions in the context of digital disruption.